Multivalent approaches and beyond: novel tools for the investigation of dopamine D2 receptor pharmacology. (July 2016) - Kopinathan, Anitha; Scammells, Peter J; Lane, J Robert; Capuano, Ben
The dopamine D2 receptor (D2 R) has been implicated in the symptomology of disorders such as schizophrenia and Parkinson's disease. Multivalent ligands provide useful tools to investigate emerging concepts of G protein-coupled receptor drug action such as allostery, bitopic binding and receptor dimerization. This review focuses on the approaches taken toward the development of multivalent ligands for the D2 R recently and highlights the challenges associated with each approach, their utility in probing D2 R function and approaches to develop new D2 R-targeting drugs. Furthermore, we extend our discussion to the possibility of designing multitarget ligands. The insights gained from such studies may provide the basis for improved therapeutic targeting of the D2 R.